Efficacy and Safety of Sonidegib in Adult Patients with Nevoid Basal Cell Carcinoma Syndrome (Gorlin Syndrome): Results from a Phase 2, Double-Blind, Randomized Trial - Lear JT; Hauschild A; Stockfleth E; Squittieri N; Basset-Seguin N; Dummer R (Dove Medical Press, 2020)
John T Lear,1 Axel Hauschild,2 Eggert Stockfleth,3 Nicholas Squittieri,4 Nicole Basset-Seguin,5 Reinhard Dummer6 1Manchester Royal Infirmary, Manchester, UK; 2Klinik Für Dermatologie, Venerologie Und Allergologie Universitätsklinikum Schleswig-Holstein, Kiel, Germany; 3Universitätshautklinik Bochum, Bochum, Germany; 4Sun Pharmaceutical Industries, Inc., Princeton, NJ, USA; 5Department of Dermatology, Hôpital Saint Louis, Paris, France; 6Skin Cancer Center University Hospital, Zürich, SwitzerlandCorrespondence: John T LearUniversity of Manchester, 46 Grafton Street, Manchester M13 9NT, UKTel +44 161 276 4173Fax +44 161 276 8881Email john.lear@srft.nhs.ukNevoid basal cell carcinoma syndrome (NBCCS), or Gorlin syndrome, is a rare hereditary disease characterized by the development of multiple cutaneous basal cell carcinomas (BCCs) from a young age.1 Loss-of-function germline mutations in the hedgehog-related patched 1 (PTCH1) tumor suppressor gene are the most common cause of NBCCS.1 The hedgehog signaling pathway plays a major role in embryonic development, and in adulthood, is involved in the renewal and maintenance of distinct tissues, including hair follicles, muscle stem cells, and gastric epithelium.2 Its abnormal activation is thought to drive the formation of both sporadic BCCs and those resulting from NBCCS.1 Patients with NBCCS inherit one inactive copy of PTCH1 and then acquire a “second-hit” mutation, resulting in hedgehog pathway activation and BCC formation.1 Mutations in Suppressor of fused (SUFU) or the PTCH1 homolog PTCH2 have also been found in a subset of patients meeting criteria for NBCCS.1,3